2020
DOI: 10.1101/2020.12.18.423568
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

blaOXA-48-like genome architecture among carbapenemase-producingEscherichia coliandKlebsiella pneumoniaein the Netherlands

Abstract: Carbapenem-hydrolyzing enzymes belonging to the OXA-48-like group are encoded by blaOXA-48-like alleles and are abundant among Enterobacterales in the Netherlands. Therefore, the objective was to investigate the characteristics, gene content, and diversity of the blaOXA-48-like carrying plasmids and chromosomes of Escherichia coli and Klebsiella pneumoniae collected in the Dutch national surveillance from 2014-2019 in comparison with genome sequences retrieved from 29 countries. By combining short-read and lon… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…To validate Flanker, demonstrate its application and provide a comparison with existing tools, we used two recent datasets of complete plasmids (derived from hybrid long-/ short-read assemblies) containing carbapenemase genes of clinical importance [23,28]. The first dataset comprised 51 complete bla OXA-48 -harbouring plasmids; 42/51 came from carbapenem-resistant Escherichia coli and Klebsiella pneumoniae isolates from patients in the Netherlands [28] and 9/51 from EuSCAPE (a European surveillance programme investigating carbapenem resistance in Enterobacterales) [23]. The second dataset comprised 50 bla KPC-2 or bla KPC-3 -(K.…”
Section: Datasetsmentioning
confidence: 99%
See 3 more Smart Citations
“…To validate Flanker, demonstrate its application and provide a comparison with existing tools, we used two recent datasets of complete plasmids (derived from hybrid long-/ short-read assemblies) containing carbapenemase genes of clinical importance [23,28]. The first dataset comprised 51 complete bla OXA-48 -harbouring plasmids; 42/51 came from carbapenem-resistant Escherichia coli and Klebsiella pneumoniae isolates from patients in the Netherlands [28] and 9/51 from EuSCAPE (a European surveillance programme investigating carbapenem resistance in Enterobacterales) [23]. The second dataset comprised 50 bla KPC-2 or bla KPC-3 -(K.…”
Section: Datasetsmentioning
confidence: 99%
“…pneumoniae carbapenemase)-harbouring plasmids in carbapenem-resistant K. pneumoniae isolated from the Netherlands [28] (8/50) and as part of the EuSCAPE study (42/50) [23]. The EuSCAPE dataset [23,29] additionally contains a large collection of short-read sequencing data for Klebsiella spp.…”
Section: Impact Statementmentioning
confidence: 99%
See 2 more Smart Citations
“…3). 2 Annotation (using Galileo AMR; see methods) of these revealed that whereas FP16 contains Tn1999, 3 FP6 contains Tn1999.2, which has been previously described as creating a strong promoter which 4 [26] of 50 hybrid assembled KPC-containing 1 plasmids, Flanker identified 8 distinct FPs over a 7200bp window upstream of bla KPC-2/3 (Fig. 4; Table 2 S2).…”
mentioning
confidence: 94%